1996
DOI: 10.1021/om9509047
|View full text |Cite
|
Sign up to set email alerts
|

Stable Palladium(0), Palladium(II), and Platinum(II) Complexes Containing a New, Multifunctional and Hemilabile Phosphino−Imino−Pyridyl Ligand:  Synthesis, Characterization, and Reactivity

Abstract: Stable palladium(0), palladium(II) and platinum(II) complexes containing a new, multifunctional and hemilabile phosphino-imino-pyridyl ligand: Synthesis, characterization and reactivity Rulke, R.E.; Kaasjager, V.E.; Wehman, P.; Elsevier, C.J.; van Leeuwen, P.W.N.M.; Vrieze, K.; Fraanje, J.; Goubitz, K.; Spek, A.L. Published in: Organometallics DOI:10.1021/om9509047Link to publication Citation for published version (APA):Rulke, R. E., Kaasjager, V. E., Wehman, P., Elsevier, C. J., van Leeuwen, P. W. N. M., Vrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
2
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 64 publications
8
49
2
1
Order By: Relevance
“…In analogy to recently reported insertions of (substituted) allenes into the palladium methyl bond of [ PdX(Me) (NIq) ] [30,31,33] it has been found that the complexes [PdX(Me)(L)] (L--NS) react rapidly and quantitatively to ~.fford ~/3-allylpalladium compounds (Scheme I). Cow duc~ivity experiments showed that the complexes are ionic in solution.…”
Section: Reactions With Cosupporting
confidence: 63%
See 2 more Smart Citations
“…In analogy to recently reported insertions of (substituted) allenes into the palladium methyl bond of [ PdX(Me) (NIq) ] [30,31,33] it has been found that the complexes [PdX(Me)(L)] (L--NS) react rapidly and quantitatively to ~.fford ~/3-allylpalladium compounds (Scheme I). Cow duc~ivity experiments showed that the complexes are ionic in solution.…”
Section: Reactions With Cosupporting
confidence: 63%
“…complexes by Gogoll etal. [47] and Vrieze and co-workers [ 30]. Therefore it was a surprise that even at low temperatures (213 K), complexes 12a, 13a, 12b.…”
Section: Reactions With Auenesmentioning
confidence: 96%
See 1 more Smart Citation
“…This can undoubtedly be explained by the stronger metal-to-carbonyl back-bonding in the imine phosphine complexes [37]. The appreciable coupling t o the phosphorus atom [38] exhibited by the aldehyde proton (complexes 1 and 2) and imine proton (complexes 3 and 4) expected as doublets) is the most remarkable aspect of the 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Vrieze and co-workers however, were able to separate a complex containing the PNN ligand and palladium(0) without any stabilizing coordinated olefins (naked palladium) [45]. Similar species could be employed as starting materials for the subsequent synthesis of olefin derivatives whose stability might arise from the interplay between the olefin coordinating capability and the ligand chelating effect.…”
Section: The Labile and Hemi-labile Ligandsmentioning
confidence: 99%